Testimonial Evidence. Perspectives and Confluences - BOIÈšĂ, Marius; IONESCU, Bogdan (Journal of Legal Studies, 2017)
The authors aim to ―drill‖ into the complex issue of the testimonial evidence, through a fresher approach, thus being interested, besides the purely legal aspect, also in the historical, sociological and even psychological perspective.